Modeling of information interconnection in a computer control system of moving objects - Kuchuk, Nina; Merlak, Viktoriia (Radìoelektronnì ì komp'ûternì sistemi (Online), 2021)
The subject of research is a pool of widgets, which provides a user interface in a computer control system for moving objects. The object of research is the process of information exchange between the components of a computer system, which are directly involved in the control of moving objects. The task of allocating resources for a pool of widgets that provide operational control of moving objects is critical. As the number of elements increases in the pool of widgets, the competition for the resources of the computer system increases significantly, respectively, the queues for the most demanded resources grow. Therefore, it is necessary to reallocate resources between requests in such a way that the priorities of requests are taken into account, and the response time of operational requests does not exceed the standard time. Such distribution cannot be realized without a model that would show the parameters of all information flows between the components, which is the purpose of this article. In doing so, the model must consider the characteristics of the pool of widgets that support the user interface. Research results. To achieve this goal, several particular tasks were solved. First, the main sets were identified that will be involved in modeling information interconnections between software components that service requests for user interface widgets in a computer system environment. Then, a diagram of informational interconnections between these sets was developed. Further, the parameters of the requests, which were initiated by the widgets, of the applications, and the fragments of the widget query service database were determined and formalized. All this made it possible to form a model of information interconnections using a tuple of obtained vectors, sets, and Boolean matrices. In the proposed mathematical model, many limitations are imposed on the elements of this tuple, associated with the characteristic features of the control module for the user interface of the computer system. Besides, the limitations associated with the functioning of the basic network of the computer system are taken into account. In the final model, Boolean matrices affecting resource allocation defined as model variables. A fast algorithm for determining the space of admissible distributions is proposed. Conclusions. The developed mathematical model determines the parameters of information flows between the components of the computer system, which are involved in the control of moving objects. This model will allow for the operational reallocation of resources between requests using the proposed fast algorithm.